quizbinf — in-class quiz for bioinformatics teaching - Käll, Lukas (SciLifeLab Serve, 2026)
Live in-class quiz tool for a KTH bioinformatics course. Students scan a QR code to answer a multiple-choice question individually, discuss it with their neighbours, then answer the same question again, letting the teacher compare the two response distributions (peer instruction). Open source, Apache-2.0: https://github.com/statisticalbiotechnology/quizbinf. This is a test deployment under active development.
Keywords: Systems Biology